Diapause in Drosophila melanogaster – Photoperiodicity, cold tolerance and metabolites. (February 2018) - Anduaga, Ane Martin; Nagy, Dora; Costa, Rodolfo; Kyriacou, Charalambos P.
Graphical abstract: Highlights: Subtle temperature changes associated with photoperiod influence diapause in D. melanogaster . Photoperiod per se plays a minor role in diapause. Developmental temperature influences levels of diapause in several European natural lines. Survival from chill-shock at −20 °C correlates with diapause not with temperature. Glucose and trehalose levels also correlate with quiescence/diapause. Abstract: Unlike many insects where photoperiod per se induces diapause, reproductive arrest in Drosophila melanogaster adult females is observed at colder temperatures and can be enhanced by shorter photoperiods. Traditional experimental protocols raise flies at 25 °C from the larval stage and then the adults are placed at 12 °C for between 12 and 28 days. After 12 days diapause levels are usually higher than at 28 days, suggesting that the flies are in a cold induced quiescence, rather than a true diapause. By raising flies at more realistic lower temperatures, we observe quite dramatic and counter-intuitive effects on diapause, whose levels nevertheless correlate with various indices of cryoprotectant metabolites as well as resistance to chill shock. We also observe that photoperiodic effects are minimised when very small temperature oscillations associated with the light-dark incubator cycles are neutralised. Our results suggest that the reported photoperiodic component of fly diapause, at least in these strains, is mostly due to thermoperiodic rather than photoperiodic stimuli. In addition, the metabolite and chill shock analyses reveal that even by 12 days, flies are entering a state that is resistant to environmental stresses.